Combined oral contraceptives and clinical aspects (Research, Society and Development, 2022)
The use of combined oral contraceptives can increase the incidence of thromboembolism reaching rates that score a risk 2 to 3 times when analyzed on a global scale. The importance of the theme is based on the lack of regular visits to the doctor, which can generate several problems, especially with regard to the use of oral contraceptives. Thus, the present study aimed to discuss combined oral contraceptives and understand the importance of going to the doctor so that he can recommend the best contraceptive, so as not to create a health risk. We sought to understand the impact that the use of combined hormonal contraceptives (CHO) causes in women, that is, the clinical aspects that their use can cause were evaluated. In the methodology, it is a literature review, to which the data collection took place in the search engines Scielo, PubMed, Lilacs and Google Scholars. The time frame of the studies took place between the years 2017 to 2021, in English and Portuguese. Of the studies collected, analyzed and included in this research, 16 remained, which were duly discussed. In the results, it was noticed that the use of combined oral contraceptives can increase the risk of thrombosis in healthy women of reproductive age.